Cadmium Removal from Phosphates of Djebel-ONK by Thermal Treatments - Belmeskine, H.; Kaemmerer, M.; Audhuy, M.; Khalaf, H. (Asian Journal of Chemistry, 2016)
In this work, the calcination of Algerian phosphate by microwave radiation is studied. Obtained results show that the dielectric constants, x' and x", of these phosphates over the frequency range from 2.4 GHz to 3.65 GHz, were in order of 3.6 and 0.36, respectively, which could be considered as admissible values for applying microwave radiation on phosphate rock calcinations. Applying the microwave radiation radiation on phosphate calcinations at laboratory scale allowed to reduce the concentration of cadmium down to 12 mg/kg and increase the P2O5 content up to 36.82%.